The Fate and Transport of Chlorinated Polyfluorinated Ether Sulfonates and Other PFAS through Industrial Wastewater Treatment Facilities in China - Liu, Shiyang; Jin, Biao; Arp, Hans Peter H; Chen, Wenwen; Liu, Yi; Zhang, Gan (Environmental science & technology, 2022)
Wastewater from certain industrial processes can be primary emission sources of per- and polyfluoroalkyl substances (PFAS) and fluorinated alternatives like chlorinated polyfluorinated ether sulfonates (Cl-PFESA). Two such industrial processes are electroplating and textile printing and dyeing (PD). This study focused on the fate of Cl-PFESA in wastewater from these two industrial processes, in comparison to other PFAS, as they went through different wastewater treatment plants located in southeast China. The total target PFAS concentrations were 520 ± 30 and 4200 ± 270 ng/L at the effluents of the PD WWTP and electroplating WWTP, respectively. Specifically, 6:2 Cl-PFESA (18%) and 8:2 Cl-PFESA (0.7%) were abundant in electroplating-wastewater. Cl-PFESA were also detected in PD wastewater but at trace concentrations and were likely present due to diffuse emissions. The dissolved-phase Cl-PFESA and PFAS mass flows through the WWTPs were fairly constant throughout both facilities. The majority of Cl-PFESA was captured by sludge sedimentation. However, there were individual treatment processes that could cause the wastewater concentrations to fluctuate, and also could lead to relative enrichment of specific Cl-PFESAs as indicated by the 6:2/8:2 Cl-PFESA ratios. Cl-PFESA and perfluoroalkyl sulfonic acids were more influenced by the investigated treatment processes than perfluorocarboxylic acids.